Voluntary organizations and nonformal adult education in Hungary: Professionalization and the discourse of deficiency. - Carol A. Pandak (Adult Education Research Conference, 1997)
This paper explores issues of professionalization and the discourse of deficiency in Hungarian voluntary organizations and nonformal adult education. The argument is made that transformational adult education, e.g., Freire and Mezirow would be useful to dispel the myth of individual deficiencies.